(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This research aimed at profit maximization of a production company located in Sabuwa Local government area of Katsina State, Nigeria using Linear programming model. The production data was obtained from the company after which a linear programming model was developed and solved using two different application software; The Ms Excel solver and PHP simplex. The results obtained showed a significant positive increase in profit. The analysis shows that for optimum profit based on the available raw materials used in this research, the company should produce 1,097 pieces of Y_2 yoghurt and 1,470 pieces of 50cl yoghurt per production. If the product mix is used, a profit of N 19,089.66 will be obtained by the company.